Economic Valuation of Medicinal Plants in Peninsular Malaysia - Muhammed Idris, Mohd Azmi (2004)
Medicinal plants are known as important non-timber forest products (NTFPs), besides bamboo and rattan, which have had great demand by rural people and the industries lately. The increasing awareness of herbal remedies and the demand of herbal products have led to crucial requirement of the local resources by the traditional medicine industries. For sustainable management of medicinal plants in the forest, there is a need to place proper values (potential and extracted values) that reveal the importance of these r esources. T hese v alues c ould i ncrease the e nvironmental b enefits, i mportant t o decision-makers, that affect the environment if optimal choices are to be made. By using market price approach, the economic values (residual value) of medicinal plants were estimated at three study sites, namely Gunung Raya, Bukit Perak and Gunung Jerai Forest Reserves at Kedah, Peninsular Malaysia. From the industrial and collectors survey, the status of the total requirement and total collection of the resources was determined. Input-use efficiency in the harvesting activities of medicinal plants was also examined. The study revealed that the average total residual values for medicinal plants per hectare in Gunung Raya Forest Reserve were RM1,654.87, RM3,746.07 at Bukit Perak Forest Reserve and RM964.53 at Gunung Jerai Forest Reserve. The total requirement of local medicinal plants by the industries (476,339 kg) per year were found exceeding the total collection of medicinal plants (103,620 kg) per year, showing the high dependency of traditional medicine industries on the local resources. From the production function analysis, the workers and harvesting tools were insufficiently used during the harvesting session. Without proper monitoring and management, the unbalanced situation of medicinal plants' demand and supply could become more critical in the years to come. Some relevant measures were recommended from this study.